THE APOLOGY STRATEGIES USED BY CUSTOMER SERVICE OFFICERS OF A LOCAL BANK IN SURABAYA - Amelia Ruth; Esther H Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2016)
In this study, the writer observed the apology strategies used by ten customer service officers of a local bank. The writer wants to find out what types of apology strategies are used by customer service officers of the local bank. The theory of apology strategy by Trosborg (1995) was used as the main theory of this research. The writer used a qualitative approach. The data were taken by recording interviews with ten customer service officers of the local bank. Then, the writer analyzed the conversation produced by these respondents. The result of the analysis, the local bank used twelve types of apology strategies. Next, the writer found the mostly used apology strategy the customer service officers employed is Repair Strategy. Overall, it was found that the customer service officers of the local bank used eight types of apology strategies and they did not use one type of apology strategy that is Promise of Forbearance